The legal status of territories subject to administration by international organisations / Bernhard Knoll. - Knoll, Bernhard (Cambridge University Press, 2008)
The international community's practice of administering territories in post-conflict environments has raised important legal questions. Using Kosovo as a case study, Bernhard Knoll analyses the identity of the administrating UN organ, the ways in which the territories under consideration have acquired partial subjectivity in international law and the nature of legal obligations in the fiduciary exercise of transitional administration developed within the League of Nations' Mandate and the UN Trusteeship systems. Knoll discusses Kosovo's internal political and constitutional order and notes the absence of some of the characteristics normally found in liberal democracies, before proposing that the UN consolidates accountability guidelines related to the protection of human rights and the development of democratic standards should it engage in the transitional administration of territory.